The Role of the Supervisory Board in the Development of Sharia Cooperatives in Aceh After the Enactment of the Sharia Financial Institutions Law - Jihad, Azka Amalia; Azmy, Khairul; A Wahab, Nazaruddin; Fauzan, Faisal; Sayuti, Azman (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Aceh is a region that applies Islamic law to all lines of government, including worship and mu'amalah. The Qanun on Sharia Financial Institutions (LKS) has been in effect since January 2019 and includes Sharia Financial Institutions. As of January 2022, there are still many cooperatives in Aceh that have not converted to sharia principles. Considering this situation, this study aims to examine the existence of the Sharia Supervisory Board (DPS) by analyzing its role and influence on sharia cooperatives in Aceh. This study employed a qualitative method, utilizing Islamic economics theory. Data were collected by means of interviews, questionnaires, and document studies. Interviews and questionnaires were carried out with respondents from the Aceh Sharia Council, the Aceh Cooperatives and SMEs Office, and the Cooperative Supervisory Board. Qanun, journal articles, and other documents relevant to the discussion were analyzed. The findings indicate that cooperatives in Aceh consist of Savings and Loans Cooperatives, Savings and Loans Units, Sharia Savings and Loans and Financing Cooperatives, and Sharia Savings and Loans and Financing Units. The number of DPS in Aceh as of 2023 is 214. The DPS has played a role in accelerating the conversion of sharia cooperatives by making several efforts while also facing various challenges and obstacles. From an Islamic economics perspective, the existence of the DPS also has an influence on increasing the conversion of sharia cooperatives in Aceh. However, the number of sharia cooperatives is still very low, only 6% of the total number of cooperatives operating in Aceh. Nevertheless, DPS still has an economic impact on the development of the sharia economy, which is an implementation of the Qanun LKS.